Myocardial Evaluation in Patients with Aortic Stenosis by Cardiac Computed Tomography - Gama, Francisco F.; Patel, Kush; Bennett, Jonathan; Aziminia, Nikoo; Pugliese, Francesca; Treibel, Thomas (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Background Aortic valve stenosis (AVS) is one of the most prevalent pathologies affecting the heart that can curtail expected survival and quality of life if not managed appropriately.Current Status Cardiac computed tomography (CT) has long played a central role in this subset, mostly for severity assessment and for procedural planning. Although not as widely accepted as other imaging modalities for functional myocardial assessment [i. e., transthoracic echocardiogram (TTE), cardiac magnetic resonance (CMR)], this technique has recently increased its clinical application in this regard.Future Outlook The ability to provide morphological, functional, tissue, and preprocedural information highlights the potential of the “all-in-one” concept of cardiac CT as a potential reality for the near future for AVS assessment. In this review article, we sought to analyze the current applications of cardiac CT that allow a full comprehensive evaluation of aortic valve disease.Key Points: Citation Format
Keywords: aortic valve; ultrasound computed tomography (US/CT); tissue characterization